Dampak Dan Upaya Memberantas Tindak Pidana Korupsi Di Lingkungan Perguruan Tinggi - Anisa Farras Azmii; Agnes Tika; Denaya Syabilla Fitri; Monika Septiyar (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Higher education is often seen as a place to shape future leaders and create positive change in society. However, corruption poses a serious threat to the integrity and purpose of higher education. This article discusses the challenges and strategies in instilling anti-corruption awareness in higher education environments. These challenges include a culture of corruption that is difficult to change, economic pressures that encourage unethical behavior, and a lack of transparency and accountability. The proposed strategy includes implementing a curriculum that promotes the values ​​of integrity, establishing an independent monitoring body, implementing a strict code of ethics, and raising awareness through campaigns and training. By implementing this strategy holistically, it is hoped that higher education can become an effective agent of change in fighting corruption and promoting good governance in society.